2001
DOI: 10.1046/j.1365-2958.2001.02645.x
|View full text |Cite
|
Sign up to set email alerts
|

Icm/Dot‐dependent upregulation of phagocytosis by Legionella pneumophila

Abstract: SummaryLegionella pneumophila is the causative agent of Legionnaires' disease, a severe pneumonia. Dependent on the icm/dot loci, L. pneumophila survives and replicates in macrophages and amoebae within a specialized phagosome that does not fuse with lysosomes. Here, we report that phagocytosis of wild-type L. pneumophila is more efficient than uptake of icm/dot mutants. Compared with the wild-type strain JR32, about 10 times fewer icm/dot mutant bacteria were recovered from HL-60 macrophages in a gentamicin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
111
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 187 publications
(115 citation statements)
references
References 70 publications
4
111
0
Order By: Relevance
“…Previously it has been shown that L. pneumophila virulence in macrophages, amoebae and mammalian models is dependent on the presence of the Dot/Icm secretion system [41][42][43] . G. mellonella larvae were infected as described above and the virulence of the wild type (WT) and a Dot/Icm-deficient strain compared.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Previously it has been shown that L. pneumophila virulence in macrophages, amoebae and mammalian models is dependent on the presence of the Dot/Icm secretion system [41][42][43] . G. mellonella larvae were infected as described above and the virulence of the wild type (WT) and a Dot/Icm-deficient strain compared.…”
Section: Representative Resultsmentioning
confidence: 99%
“…3 LCVs avoid fusion with lysosomes (6), intercept vesicular traffic at endoplasmic reticulum (ER) exit sites (7), and fuse with the ER (8 -10). The uptake of L. pneumophila and formation of LCVs in macrophages and amoebae depends on the Icm/Dot type IV secretion system (T4SS) (11)(12)(13)(14). Although more than 100 Icm/Dot substrates ("effector" proteins) have been identified to date, only few are functionally characterized, including effectors that interfere with host cell signal transduction, vesicle trafficking, or apoptotic pathways (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Phagocytosis and intracellular replication of L. pneumophila is promoted by the intracellular multiplication/ defective organelle trafficking (Icm/Dot) type IV secretion system (T4SS) (Hilbi et al, 2001;Segal et al, 1998;Vogel et al, 1998), a conjugation apparatus which translocates more than 40 putative 'effector' proteins into host cells (Brüggemann et al, 2006;Nagai & Roy, 2003). The Icm/Dot T4SS is also required for L. pneumophila to survive and grow on agar plates impregnated with Acanthamoeba castellanii (Albers et al, 2005).…”
Section: Introductionmentioning
confidence: 99%